The Influence of Transformational Leadership and Work Facilities for Airport Rescue and Fire Fighting Personnel (ARFF) on Personnel Performance with Motivation as a Mediating Variable (Case Study of Soekarno Hatta Airport) - Agung Brahmantyo; Rohana Sitanggang; Erna S Widodo (Dinasti Review, 2025)
Soekarno-Hatta International Airport is the main airport in Indonesia located in Cengkareng, West Jakarta. In the aviation industry, all parties such as airlines, airport managers and air traffic controllers must comply with strict safety and security standards. The Airport Rescue And Fire Fighting Unit (ARFF) at Soekarno-Hatta Airport has an important role in handling emergencies in accordance with national and international regulations. ARFF main tasks include saving lives and property as well as fighting fires in the airport area. However, some of the challenges faced by this unit are related to human resources, facilities and leadership. This research shows that ARFF performance is very dependent on improvements in the aspects of people, facilities and leadership to increase readiness and response in dealing with emergency incidents at airports. The research methodology used is quantitative data. Meanwhile, the data source used in this research is primary data, namely data obtained from Angkasa Pura II employees who work in the ARFF division of Soekarno Hatta Airport and using analytical tools SEM PLS And Smart PLS. This research aims to examine the influence of transformational leadership and work facilities on the performance of ARFF personnel at Soekarno-Hatta Airport, with motivation as a mediating variable.